SyNTHESIS OF GALLIUM SULFATE - V. Yu. Proydakova; S. V. Kuznetsov; V. V. Voronov; P. Fedorov (Тонкие химические технологии, 2017)
Trivalent gallium compounds are structural analogs of the elements with variable valency in (+3) oxidation state that can be used as cathode materials for electrochemical power devices (iron, vanadium, chromium). Literature data about gallium(III) sulfate are quite scarce. So, we developed a preparation technique for synthesizing Ga2(SO4)3 from Ga(CH3COO)2OH as a starting material. The latter was dissolved in sulfuric acid. Then gallium(III) sulfate hydrate was precipitated under cooling. The obtained precipitate is extremely hygroscopic, and it deliquesces quickly under aerobic ambient conditions. The synthesized gallium(III) sulfate hydrate was dried on the filter and then kept in vacuum at 10-2 torr for two hours to remove traces of water and acetic acid. Gallium(III) sulfate, its intermediates and products of its thermal treatment were studied by differential thermal analysis (DTA) and X-ray diffraction phase analysis. The content of crystallization water in gallium(III) sulfate hydrate was determined, and the composition of the crystallohydrate was established as Ga2(SO4)3·18H2O. (The original X-ray diffraction pattern of the latter is disclosed below in this paper.) The mentioned crystallohydrate lost its water in six steps within 40-350 °С temperature range and formed anhydrous Ga2(SO4)3, which, in turn, decomposed at 700 °С and produced nanocrystalline gallium oxide, Ga2O3. Anhydrous gallium(III) sulfate is slightly hygroscopic, so it should be stored in a desiccator. It was found that propanol-2 (isopropanol) can be used to precipitate gallium(III) sulfate from aqueous sulfuric acid: isopropanol extracts acetic acid and, thus, exhibits salting-out activity. The formed amorphous precipitate partially loses its mass when heated up to 400 °С. However, a single phase Ga2(SO4)3 specimen could not be synthesized by this method. Considering similarities between gallium and indium, it can be assumed that Ga2(SO4)3 precipitate is contaminated by gallium oxosulfate.